A CONCEPTUAL TOOL FOR ASSESSING CLIENT PERFORMANCE IN THE CONSTRUCTION PROJECT COALITION - Robby Soetanto; David G. Proverbs; Gary D. Holt (Civil Engineering Dimension, 2002)
Due to the significant impact of client performance on overall project performance and the interdependence of participant%5C%27s performance in the construction project coalition %28i.e. clients%2C designers and constructors%29%2C there is a need to establish client performance measures. Based on data collected from in-depth interviews with nineteen UK architects and nine UK contractors%2C a generic tool for the on-going formal assessment of client performance is presented. It was found that this approach to performance assessment %28i.e. from the view point of other%2C non-client coalition participants%29 should lead to improved project relationships. Data analysis showed that in addition to %5C%27harder%5C%27 measures such as understanding of project requirements and finance%2C other%2C %5C%27softer%5C%27 measures of client performance %28e.g. attitude%29 were worthy of consideration since they determine the quality of participant relationships. It is recommended that the tool be used to promote more effective client performance and thus enhance coalition relationships%2C enabling continuous improvement. The ultimate aim is to develop similar tools for the assessment of all coalition participants based on a culture of openness and trust. Abstract in Bahasa Indonesia : assessment+tool%2C+coalition+participants%2C+client+performance%2C+perceptions%2C+performance+measures%2C+satisfaction.